DONOR’S BONE MARROW CELLS AS REGULATORS OF IMMUNE TOLERANCE INDUCTION IN RECIPIENT’S OF ALLOGENIC ORGANS - N. A. Onishchenko; S. D. Artamonov; M. E. Krasheninnikov; L. V. Bashkina; A. O. Nikol’skaya; M. Y. Shagidulin; D. A. Velikiy (Вестник трансплантологии и искусственных органов)
In this review the modern conception of induction of immune tolerance was presented. Possibilities of immune tolerance induction after organs transplantation by allogenic bone marrow cells were considered.